2020
DOI: 10.1523/jneurosci.1772-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Molecular Players at the Cholinergic Efferent Synapse of the Zebrafish Lateral Line

Abstract: The lateral line (LL) is a sensory system that allows fish and amphibians to detect water currents. LL responsiveness to external stimuli is modulated by descending efferent neurons. LL efferent modulation aids the animal to distinguish between external and self-generated stimuli, maintaining sensitivity to relevant cues. One of the main components of the efferent system is cholinergic, the activation of which inhibits afferent activity. Since LL hair cells (HC) share structural, functional and molecular simil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 106 publications
1
24
0
Order By: Relevance
“…While our data do not directly support this idea, we speculate that reduced glutamatergic transmission in mechanically overstimulated neuromasts may be a consequence of damaged hair bundles and impaired mechanotransduction (Zhang et al, 2018). Alternatively, cholinergic efferent feedback, which has been shown to hyperpolarize lateral-line hair cells, may reduce hair-cell excitability during sustained strong current exposure to protect against excess glutamate release, excitotoxic damage, and synapse loss (Carpaneto Freixas et al, 2021). Interestingly, presynaptic ribbons were not similarly enlarged, but instead showed a modest reduction in size following mechanical injury.…”
Section: Discussionmentioning
confidence: 99%
“…While our data do not directly support this idea, we speculate that reduced glutamatergic transmission in mechanically overstimulated neuromasts may be a consequence of damaged hair bundles and impaired mechanotransduction (Zhang et al, 2018). Alternatively, cholinergic efferent feedback, which has been shown to hyperpolarize lateral-line hair cells, may reduce hair-cell excitability during sustained strong current exposure to protect against excess glutamate release, excitotoxic damage, and synapse loss (Carpaneto Freixas et al, 2021). Interestingly, presynaptic ribbons were not similarly enlarged, but instead showed a modest reduction in size following mechanical injury.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments using knockout larvae establish that the α9 cholinergic receptor subunit, which is also conserved in the hair cells of the mammalian inner ear, is pivotal for the suppression of reafferent mechanosensation in the neuromast. Recent work has determined that α9 subunits are expressed in zebrafish neuromasts, and that these can form functional homomeric acetylcholine-sensitive receptors in heterologous preparations (Carpaneto Freixas et al, 2021). Furthermore, using calcium imaging, this study showed that application of acetylcholine reduces calcium signals evoked by hair cell stimulation, and that this effect is blocked by apamin, a selective blocker of small-conductance calcium-activated potassium (SK) channels.…”
Section: Discussionmentioning
confidence: 99%
“…One originating from the cholinergic Octavolateral Efferent Nucleus (OEN) in the hindbrain and the other from the Dopaminergic Efferent to the Lateral Line (DELL) in the ventral hypothalamus (Bricaud et al, 2001; Metcalfe et al, 1985). Further, acetylcholine has been shown to inhibit hair cell activity (Carpaneto Freixas et al, 2021; Dawkins et al, 2005), making the OEN the most likely source of reafferent suppression. At the synaptic level, ideas about how acetylcholine may inhibit hair cells come from work done in the mammalian inner ear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish, for example, have hair cells arranged in a mechanosensory lateral line organ that is used, in part, to avoid capture. Recently it was demonstrated that these lateral line hair cells utilize α9 nAChRs at the efferent synapse to mediate ACh neurotransmission ( Carpaneto Freixas et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%